Expression of MTA1 promotes motility and invasiveness of PANC-1 pancreatic carcinoma cells - Hofer, M D (Nature Publishing Group, 2004)
The human metastasis-associated protein 1 (MTA1) is a constituent of the nucleosome-remodelling and -deacetylation complex. Its expression has been correlated with the invasion and metastasis of epithelial neoplasms. To address the functional consequences of MTA1 expression in pancreatic carcinoma cells, we have established PANC-1 pancreatic carcinoma cells that stably express MTA1 as an enhanced green fluorescent fusion protein (EGFP–MTA1). Here, we demonstrate that heterologous expression of EGFP–MTA1 markedly enhanced the cellular motility and the invasive penetration of epithelial barriers by the cells. Expression of EGFP-MTA1 had no effect on substrate-independent growth, but reduced substrate-dependent cell proliferation. In addition, the organisation of the cytokeratin filament system and the localisation of the actin cytoskeleton-associated protein IQGAP1 were distinctly altered in EGFP–MTA1-expressing cells. These results indicate that enhanced expression of MTA1 promotes the acquisition of an invasive, metastatic phenotype, and thus enhances the malignancy of pancreatic adenocarcinoma cells by modulation of the cytoskeleton.